The Analysis of Pyrophyllite Quality as a Potential Industrial Raw Material in Argotirto Area, Sumbermanjing Wetan District, Malang Regency, East Java, Indonesia - Winarno, Tri; Martadiastuti, Vanadia; Puspitasari, Evie Irvinia (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
The Argotirto area, Sumbermanjing Wetan District, Malang Regency, East Java is one of area which had industrial mineral, namely pyrophyllite. Pyrophyllite minerals in this area were generally found in rocks that have been altered by hydrothermal alteration. Pyrophyllite is an industrial mineral that can be used as a raw material in various industries. This research aims to determine the geological conditions, physical properties, mineralogical and geochemical properties of pyrophyllite in the research area and to determine the quality of pyrophyllite as a potential industrial raw material. The methods used in this research were megascopic analysis, petrographic analysis, X-Ray Diffraction (XRD) analysis, and X-Ray Fluorescene (XRF), and the quality assessment of pyrophyllite using the standard of PT Gunung Bale, SNI No. 15-1023-1989, and SNI No. 15-1325-1989. The lithology in the study area consists of basaltic lava, andesite breccia, dacitic tuff breccia, dacite intrusion, and limestone. Pyrophyllite in the study area has a quality ranging from low grade to high grade. The EIP sample is classified as high grade quality and can be used as raw materials for the refractory industry, class I refractory materials, and materials for making fine ceramics. The WSP sample is classified as medium grade quality, and can be used as class III refractory materials. The DSP sample is classified as low grade quality, and can be used as a class III refractory material.